An exploratory study of how high-contact services conduct online marketing communications - Ho, Cang Ning (2021)
This study explores how high-contact services conduct online marketing communications, such as the media platforms used, the frequency at which online marketing communications is conducted, the content communicated and analyses how these efforts achieve marketing goals.